A case of supernumerary derivative chromosome 22 syndrome in a child - R. V. Olennikova; O. I. Rytenkova; A. N. Volkov (Фундаментальная и клиническая медицина, 2023)
Here we describe a rare case of an abnormal karyotype with a supernumerary derivative chromosome der(22)t(11;22), associated with Emanuel syndrome, in a boy aged 1 year. Familial cytogenetic analysis revealed the maternal origin of the anomaly from reciprocal translocation t(11;22) (q23;q11.2). At the time of the examination, the child had numerous anomalies of development, facial dysmorphia, and a small size of the external genitalia. In addition, there was a pronounced delay in psychomotor development because of the brain damage. We made an attempt to perform a comprehensive analysis of the risks to the patient's health by generalizing the cases of Emanuel syndrome described in the literature.